Three-dimensional power Doppler ultrasound evaluation of placental blood flow in normal monochorionic diamniotic twin pregnancies - Wei Sun; Shaowei Yin; Qiuju Wei; Ying Zhang; Zeyu Yang; Ailu Cai; Yu Wang; Wenjia Lei (BMC, 2018)
Abstract Background Monochorionic diamniotic (MCDA) twin pregnancies are at higher risk of adverse outcomes and complications, which are attributed to the influence of placental morphology in MCDA twins. Monitoring of placental function is an important index for clinical decisions. The aim of our study was to evaluate the placental blood flow estimated using three-dimensional power Doppler (3D-PD) ultrasound and the vascular indices distribution with gestational age (GA) in normal MCDA twin pregnancies. Methods One hundred four MCDA twin pregnancies and 106 singleton pregnancies (GA range, 14-32 weeks) were included in this prospective study. 3D-PD volume data of each fetus was obtained separately from the placenta at the site of umbilical cord insertion. We analyzed the volume data using sonobiopsy technique. The placental vascularization index (VI), flow index (FI) and vascularizationflow index (VFI), were auto-calculated. The means and standard deviation values of three vascular indices per fetus were calculated and regression analysis of the vascular indices as a function of GA was performed in twin pregnancies. The vascular indices of twin and singleton pregnancies were compared using independent t-test. Results There were no significant differences in VI, FI or VFI among the fetuses of twins (p > 0.05). These vascular indices increased over the course of pregnancy (p < 0.05). We obtained the regression equations for the indices as a function of GA in days: VI = exp. (4.369-28.533/GA) (R 2  = 0.699, p < 0.05), FI = exp. (3.916-13.003/GA) (R 2  = 0.511, p < 0.05), and VFI = exp. (3.577-37.468/GA) (R 2  = 0.675, p < 0.05). There were no significant differences in three vascular indices between MCDA twin and singleton groups (p > 0.05). Conclusions 3D-PD placental data using sonobiopsy technique could reflect the placental blood flow of each twin, which could be applied to the study of placental perfusion in MCDA twin pregnancies. This study also presented the vascular indices distribution with GA in normal twin pregnancies, which might be useful for early detection of MCDA complications.